A validation study of the UGT1A4 rs2011404 variant and the risk of anti‐tuberculosis drug‐induced hepatotoxicity in an Eastern Chinese Han population. (27th May 2021) - Zhu, Jia; Liu, Wenpei; Zhang, Meiling; Lu, Lihuan; Pan, Hongqiu; He, Xiaomin; Wang, Nannan; Yang, Miaomiao; Yi, Honggang; Tang, Shaowen
Abstract: What is known and objective: Anti‐tuberculosis (anti‐TB) drug‐induced hepatotoxicity (ATDH) is a serious adverse drug reaction. A recent study found that the rs2011404 variant of uridine 5′‐diphospho‐glucuronosyl‐transferase 1A4 (UGT1A4) is a marker of susceptibility to ATDH. The present study aimed to validate this relationship in an Eastern Chinese Han anti‐TB treatment population. Methods: A 1:4 matched case‐control study was conducted among anti‐TB treatment patients in four regions of Jiangsu. ATDH was diagnosed based on the criteria from the Chinese Society of Hepatology and the updated Roussel Uclaf Causality Assessment Method. A conditional logistic regression model was used to estimate the association between rs2011404 genotypes and the risk of ATDH using odds ratios (ORs) with 95% confidence intervals (95% CIs) and smoking, drinking, hepatoprotectant use and liver diseases as covariates. Results and discussion: A total of 202 ATDH cases and 808 controls were matched according to age, sex and treatment history. After correcting for potential confounding factors, conditional logistic regression analysis indicated no significant differences in genotypes between the two groups (CC vs. TC: OR = 0.933, 95% CI: 0.457–1.905, p = 0.849). Subgroup analysis suggested that patients carrying the CC genotype at rs2011404 in UGT1A4 were at a reduced risk of moderate or severe liver injury (OR = 0.293, 95% CI: 0.093–0.921, p = 0.036). What is new and conclusion: Based on a 1:4 individual matched case‐control study, possessing the CC genotype at rs2011404 of the UGT1A4 gene reduces the risk of moderate or severe liver injury in Eastern Chinese Han patients receiving anti‐TB treatment. Further research is warranted to explain the role of the UGT1A4 gene and its contribution to individual differences in susceptibility to ATDH. Abstract : The findings suggest that possessing the CC genotype at rs2011404 of the UGT1A4 gene reduces the risk of moderate or severe liver injury in Eastern Chinese Han patients receiving anti‐TB treatment.